Switching on a Nontraditional Enzymatic Base – Deprotonation by Serine in the ent-Kaurene Synthase from Bradyrhizobium japonicum - Jia, Meirong (ACS Catal, 2019)
Terpene synthases often catalyze complex carbocation cascade reactions. It has been previously shown that single residue switches involving replacement of a key aliphatic residue with serine or threonine can “short-circuit” such reactions, presumed to act indirectly via dipole stabilization of intermediate carbocations. Here a similar switch was found in the structurally characterized ent-kaurene synthase from Bradyrhizobium japonicum. Application of a recently developed computational approach to terpene synthases, TerDockin, surprisingly indicates direct action of the introduced serine hydroxyl as a catalytic base. Notably, this model suggests alternative interpretation of previous results, and potential routes towards reengineering terpene synthase activity more generally.